Religion, Capitalism, and Cannibalism: An analysis of “An Orison of Sonmi-451” - da Silva, Gustavo Ruiz; Gadelha Figueiredo Jr., Eberval (Revista PHILIA | Filosofia, Literatura & Arte, 2025)
This paper analyses the fifth story from David Mitchell’s novel Cloud Atlas (2004), concerning Sonmi 451’s life, resistance, and death in Nea So Copros (a dystopian futuristic plutocratic State set in Korea). We will briefly present the novel’s structure, along with insights from other commentators. Afterwards, there shall be three sections: 1. On Religion, 2. On Capitalism, and 3. On Cannibalism, addressing three types of oppression: (i.) ideological control through religious discourse; (ii.) labour-related subjugation, involving the systematic extraction of economic productivity and political obedience; and (iii.) corporal domination, as fabricants (non-naturally born) are viewed as exploitable product-bodies. We hypothesise that Mitchell describes a full dispositif when it comes to their means of production, surplus extraction, and power relations.